Factors impacting university students' engagement with classroom activities: qualitative study. (1st January 2014) - Kashif, Muhammad; Basharat, Sara
Student engagement is a topic of interest to higher education policymakers due to lack of student interest with classroom activities. This study aims to explore the factors which contribute towards university students' engagement with classroom activities in a developing country context of Pakistan. For this exploratory study, naturalist-paradigm is followed and qualitative data is collected through detailed interviews, conducted with students of a local university in Pakistan. The personality of instructor, courses with practical relevance, lecture contents, students' intrinsic motivation, and discussion-based classes are found to influence the extent of engagement. This research will be useful for university professors and administrators who are striving hard to find ways to engage university students with classroom activities.